The rise of Indie-cinema in the USA (Journal of Philosophy Culture and Political Science, 2018)
This article reveals the features of the existence of independent cinema in the United States. The author considers the concept of independent cinema from the point of view of both universal perception and from the point of view of the desired, plunging into the origins of the formation of American cinema art in general.The author also studies experimental US cinematography, which stands on the sidelines, away from the so-called mainstream and finds that such a movie defines the national core of American cinema, sees in it the beginning of a new direction and new cinematic thinking of Hollywood.Hollywood, as a conveyor of the same type of work, according to the author, can not do something close to real art and therefore the most interesting in the US cinema to look for in the marginal and low-budget cinema of America.In passing, the creative work of original and little-known directors of independent cinema in the United States, which contributed a lot to the culture of a kind of indie genre. Analyzing American avant-gardists such as Maya Deren, the author is interested in the shaky position of the European direction of independent cinema in the US, such non-commercial genres as surrealism, and concludes that American cinema has lost its non-conformist spirit, guided by the search for the viewer.Key words: Independent cinema, cinema, Cassavetes, Anger, Mekas, Deren, Brakhage.